Cloud-based order tracking system for microenterprises in the carpet cleaning industry: design, deployment, and evaluation - Karatas, Ferhat; Aytac, Sevcan (Springer Heidelberg, 2026)
Service-oriented microenterprises often struggle with manual order handling, fragmented customer records, and inefficient delivery coordination, which limit operational efficiency and service quality. This study presents the design, deployment, and evaluation of a cloud-based order tracking system adopted by over 500 small and microenterprises in the carpet cleaning industry. Leveraging Software-as-a-Service (SaaS) architecture and open interoperability standards, the system streamlines manual processes, improves route optimization, and enhances customer communication. To assess its real-world impact, detailed operational data were analyzed from 50 early-adopting firms with sufficiently complete pre-implementation and post-implementation records. The findings suggested improvements in order processing time, notification practices, delivery-related operations, and overall service coordination, while customer satisfaction was described based on post-implementation survey feedback. Applying the Technology-Organization-Environment (TOE) framework, this research explores the key drivers and barriers to adoption in resource-constrained service firms. Findings suggest that small service businesses can achieve enterprise-grade automation through scalable, modular, and cost-effective cloud solutions, demonstrating the broader potential of digital transformation in microenterprise service sectors.
Keywords: Cloud-Based System; Order Tracking; Microenterprise; Carpet Cleaning Industry; Toe Framework